'The Charm of a Thousand Years': exploring tourists' perspectives of the 'culture-nature value' of the Humble Administrator's Garden, Suzhou, China. (17th November 2021) - Zhang, Rouran; Wang, Jianing; Brown, Steve
ABSTRACT: Despite the promulgation of the UNESCO Convention Concerning the Protection of the World Cultural and Natural Heritage in 1972, widely lauded for being the first international convention to include natural and cultural heritage, the separation of cultural and natural heritage persists. Equally, within the top-down 'authorised' global and national heritage systems, the values of the elite and powerful continue to be emphasised while the understanding of heritage by the general public is often downplayed or ignored. This paper analyses the travel journals of tourists who have recently visited the 拙政园 (Humble Administrator's Garden), China, in order to explore visitor understanding of the cultural and natural values of this World Heritage listed place. The findings indicate that tourists' experiences are connected to their personal memories, feelings and emotions in ways that integrate cultural and natural heritage meanings and values. Such interconnected 'naturecultures' experienced by individual tourists, we argue, is more emotional and powerful than the official UNESCO and state-sanctioned narrative.